Keeping company [videorecording (DVD)] - Wallace, Josh; Das, Devin; Das, Devin; Grodnik, Jacob; Bharoocha, Ahmed; Vigman, Gillian, 1972- (1091 Pictures, 2022)
A fateful chain of events begins to unravel after two brash insurance salesmen go knocking on the wrong door and find themselves trapped inside of a serial killer's basement, putting their lives and their jobs on the line.